Mechanical and biological characterization of alkaline substituted orthophosphate bone substitutes containing meta- and diphosphates. (25th September 2017) - Klein, Moritz; Laschke, Matthias W; Holstein, Jörg H; Histing, Tina; Pohlemann, Tim; Menger, Michael D; Garcia, Patric
Abstract: Despite the growing knowledge on the mechanisms of fracture healing, bone defects often do not heal in a timely manner. Clinically, tricalcium phosphate (TCP) bone substitutes are used to fill bone defects and promote bone healing. However, the degradation rate of these implants is often too slow for sufficient bone replacement. The use of calcium phosphate material with the crystalline phase Ca10 [K/Na](PO4 )7 containing different amounts of di- and metaphosphates may overcome this problem, because these materials show an accelerated degradation. Therefore, we generated alkaline substituted Ca–P scaffolds with different amounts of ortho-, di- and metaphosphates. The degradation of these materials was analyzed in TRIS–HCl buffer solution in vitro . Moreover, we measured the compressive strength and porosity of the scaffolds by micro-CT analysis. The biocompatibility of the scaffolds was evaluated in vivo in the mouse dorsal skinfold chamber by means of intravital fluorescence microscopy and histology. We found that higher amounts of incorporated di- and metaphosphates increase the degradation rate and compressive strength of the scaffolds without inducing a stronger leukocytic inflammatory host tissue reaction after implantation. Histological analyses confirmed the good biocompatibility of the scaffolds containing di- and metaphosphates. In summary, this study demonstrates that the compressive strength and degradation rate of Ca–P scaffolds can be improved by incorporation of di- and metaphosphates without affecting their good biocompatibility. Hence, this material modification may be particularly beneficial for the treatment of metaphyseal bone defects in weight bearing locations.